An Afro-Christian contextual analysis of presidential pardon in post-colonial African politics - B.O. Igboin (Acta Theologica)
Presidential or royal pardon is an age-long practice in precolonial Africa as well as in biblical times. This practice has never been without criticisms because of how, and on whom the pardon is granted. The trial of Jesus has been vastly studied within an African theo-interpretive model. However, the demand for the release of Barabbas rather than Jesus has not been adequately studied in a contextual or comparative theo-political manner in Africa. This is the thrust of this article. Using the desktop method, the article argues that presidential pardon granted to convicted criminals who are not allowed to serve judicial punishment is a stimulant for inveterate corruption in the polity. The theoretical argument of this article is that many African political leaders often resort to this kind of pardon that has adversely affected the polity. The significance of this is that this behaviour emboldens political leaders to continue to corrupt the system with dire consequences for the people.